2021
DOI: 10.1111/hojo.12408
|View full text |Cite
|
Sign up to set email alerts
|

‘We've all got a big story’: Experiences of a Trauma‐Informed Intervention in Prison

Abstract: This article examines women's experiences of participating in ‘Healing Trauma’; a gender‐responsive, trauma‐informed intervention delivered in women's prisons in England. Victimisation and trauma are prevalent among women in the justice system but are not perceived to be amenable to criminal justice intervention, and there are compelling arguments that correctional environments are inappropriate settings for trauma‐informed programmes. This article analyses focus group discussions with women who completed Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Studies of women’s experiences of ‘Healing Trauma’ (HT), a trauma-informed intervention delivered in prisons in England and Wales found that, in focus groups, the women said that the programme had the potential to give them opportunities to heal from trauma, and this was crucial given their generally negative experience of imprisonment. The women also highlighted areas of the programme that could be developed, such as follow-up sessions and holistic support outside the group (Petrillo, 2021). 3 Studies in the United States have shown similar promise: Rousseau et al (2019) report on an evaluation of a trauma-informed programme that integrates psycho-education and mindfulness developed by the organisation YogaHOPE.…”
Section: Can Prisons Be ‘Trauma-informed’?mentioning
confidence: 99%
“…Studies of women’s experiences of ‘Healing Trauma’ (HT), a trauma-informed intervention delivered in prisons in England and Wales found that, in focus groups, the women said that the programme had the potential to give them opportunities to heal from trauma, and this was crucial given their generally negative experience of imprisonment. The women also highlighted areas of the programme that could be developed, such as follow-up sessions and holistic support outside the group (Petrillo, 2021). 3 Studies in the United States have shown similar promise: Rousseau et al (2019) report on an evaluation of a trauma-informed programme that integrates psycho-education and mindfulness developed by the organisation YogaHOPE.…”
Section: Can Prisons Be ‘Trauma-informed’?mentioning
confidence: 99%
“…The Female Offender Strategy (Ministry of Justice, 2018) emphasised the importance of implementing a trauma informed approach to working with women within the justice system. This has seen several interventions such as “Becoming Trauma Informed” and the Compassionate Recovery and Neurological Empowerment (CRANE) being implemented (Auty et al , 2022; Mahoney et al , 2022; Petrillo, 2021).…”
Section: Factors That May Increase the Proclivity Of Suicidal Behavioursmentioning
confidence: 99%
“…For example, Bevan's (2022) research on the operationalisation of TIP in the women's prison in Aotearoa/New Zealand highlights the risk that these programs may re-traumatise women and position them as responsible for their trauma. On the other hand, Petrillo's (2021) research on the small pilot 'Healing Trauma' program in English prisons found that participating women reported largely beneficial experiences. While Petrillo concedes that abolitionist feminist concerns about gender-responsive programs contributing to prison expansion are difficult to counter, she argues the reality is that women are in the system and they need support.…”
Section: The Emergence Of Trauma-informed Prisons and Carceral Legaci...mentioning
confidence: 99%